2010
DOI: 10.4161/cbt.9.4.10643
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of angiotensin II type 2 receptor gene induces cell death in lung adenocarcinoma cells

Abstract: The endogenous angiotensin II (Ang II) type 2 receptor (AT2) has been shown to mediate apoptosis in cardiovascular tissues. Thus, the aim of this study was to explore the anti-cancer effect of AT2 over-expression on lung adenocarcinoma cells in vitro using adenoviral (Ad), FuGENE, and nanoparticle vectors. All three gene transfection methods efficiently transfected AT2 cDNA into lung cancer cells but caused minimal gene transfection in normal lung epithelial cells. Ad-AT2 significantly attenuated multiple huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 45 publications
5
53
1
Order By: Relevance
“…In recent years, the role of the renin-angiotensin system (RAS) in tumor progression or metastasis has been extensively characterized (3)(4)(5)(6)(7)(8). Changes in the expression of RAS components, particularly in local tumor tissue, appear to correlate with tumor grade and clinical outcome (9).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the role of the renin-angiotensin system (RAS) in tumor progression or metastasis has been extensively characterized (3)(4)(5)(6)(7)(8). Changes in the expression of RAS components, particularly in local tumor tissue, appear to correlate with tumor grade and clinical outcome (9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pancreatic ductal carcinoma cells, placed in culture with fibroblasts transfected with the AT2 receptors, showed a slower growth rate, whereas overexpression of AT2 receptors in lung cancer cells induced cell death via apoptosis. [11,12] These data seem to support an antitumour profile by AT2 receptors. Recent experimental data, however, have demonstrated that, under certain pathological conditions, AT2 receptors may play an AT1 phenotype, losing their properties of vasodilation and antiangiogenesis and assuming a pro-angiogenic property.…”
mentioning
confidence: 70%
“…AT2R over-expression effectively attenuates the growth of lung adenocarcinoma cells through intrinsic apoptosis (Pickel et al, 2010). However, AT2R may also promote tumorigenesis and cell proliferation (Kanehira et al, 2005;Pickel et al, 2010). Thus, the potential role of hypoxia-induced RAS dysregulation should be examined.…”
Section: Discussionmentioning
confidence: 99%
“…ANG II promotes tumor proliferation, migration, angiogenesis, and metastasis primarily through AT1R (Egami et al, 2003;Fujita et al, 2002Fujita et al, , 2005. AT2R may counter the activities of AT1R (Pickel et al, 2010). However, AT2R can also promote tumor angiogenesis (Pickel et al, 2010) and proliferation (Kanehira et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation